Sampling algorithms - Tille, Yves (New York: Springer, 2006)
Over the last few decades, important progresses in the methods of sampling have been achieved. This book draws up an inventory of new methods that can be useful for selecting samples. Forty-six sampling methods are described in the framework of general theory. The algorithms are described rigorously, which allows implementing directly the described methods. This book is aimed at experienced statisticians who are familiar with the theory of survey sampling.
Introduction and overview -- Population, sample and sampling design -- Sampling algorithms -- Simple random sampling -- Unequal probability exponential designs -- The splitting method -- More on unequal probability designs -- Balanced sampling -- An example of the Cube method
Includes index and bibliography
Keywords: Sampling (Statistics)